Optimisation using Central Composite Design for Adsorption of Virgin Coconut Oil - Erna - Yuliwati; Nurlailah - Nurlailah; Dian Kharismadewi (Reaktor, 2020)
Development of coconut-based industries in Indonesia has excellent prospects, especially Virgin Coconut Oil (VCO) as a nutritional supplement for health. In order to produce high quality of VCO, this research developed activated carbon betung bamboo (Dendrocalamus asper) as bio-adsorbent in adsorption process. The composition of bio-adsorbent in chromatographic column has been optimized using central composite design (CCD). Bio-adsorbent were characterised by using Scanning electron microscopy (SEM) and fourier transform infrared spectroscopy (FTIR), the average poresize of 1.59 μm was calculated using equation. Adsorption isotherm data have been described by Freundlich and Langmuir models and resulted the adsorption equilibrium constant of kf of 80.68 mg g-1and kL of 0.056 L mg-1. Pseudo-second-order kinetic model resulted adsorption rate constant, k of 0.004 g mg-1 min-1 with a good fitting R2 of 0.997. This optimum process condition was achieved on adsorption time of 33 hours, 150 gr of bio-adsorbent and 411.75gr of adsorbed (neat VCO), that produced odorless and colorless VCO, density of 0.91630gr/mL and FFA concentration of 0,0602 %, which. were fulfil the standard of SNI-3741-2013 and APCC.Keywords: CCD, adsorption; fixed bed column; bio-adsorbent; Dendrocalamus asper